Predikativy i predikaty sostojanija v russkom jazyke - Cimmerling, Anton Vladimirovič (Slavistična revija, 2018)
This paper discusses the syntax and semantics of Russian constructions with non-agreeing predicatives. I show that the constructions NDAT - VLINK - PRED (dative-predicative structures, DPS) and NNOM-VLINK - PRED are used to express the meaning of inner state-i.e., stage-level predicates linked to an animate subject. Pospelov's claim that all predicatives are non-agreeing elements is correct, but Russian supports the regular homonymy of predicatives vs. adjectival elements.
Keywords: notranje stanje doživljalca; povedkovnik; Russian; ruščina; semantics; semantika; skladnja; syntax; zunanje okoliščine